Accuracy assessment of the Ring of Fire system for on-site aerodynamic drag measurements - Spoelstra, A. (Journal of Science and Cycling, 2019)
Nowadays, professional and ambitious amateur athletes are seeking small aerodynamic improvements relying on wind tunnel balance measurements, velodrome tests, and outdoor field tests. Many new companies have specialized in offering such testing days, which underlines the growing importance and demand on improving the aerodynamic ef?ciency. However, one of the big drawbacks of these traditional testing methods is that they act as a black box, as only overall drag data can be extracted, without visualizing the flow structures around the cyclist, which could be used to identify the region that offers the greatest potential. In order to gain further insight into the flow around the cyclist, other approaches need to be employed. One of the methods is CFD (Computational Fluid Dynamics) which allows simulating the airflow around the cyclist numerically. Even though this method shows the capability of simulating complex flows in sports, as shown in Gardan et al. (2017), it is often limited to an idealized environment without modelling the transiting behaviour occurring in most sports, like the pedalling motion of a cyclist.